Break force and tensile strength relationships for curved faced tablets subject to diametrical compression - Shang, C.; Sinka, I.C.; Jayaraman, B.; Pan, J. (International journal of pharmaceutics, 2013)
The break force of flat faced tablets subject to diametrical compression (often referred to as “hardness”) can be related to the tensile strength of the material using the Hertz contact theory. For curved tablets analytical solutions do not exist and an empirical equation developed by Pitt and Newton (1988) is usually used. In this paper we measure the break force of curved faced tablets having a range of curvatures pressed at various compaction forces. An empirical equation is proposed to relate the break force of curved faced tablets to the material tensile strength. The proposed equation is simplified and reduced to a form that is consistent with developed by Hertz theory for flat faced tablets.